2004
DOI: 10.1210/jc.2003-031747
|View full text |Cite
|
Sign up to set email alerts
|

Elevation in Serum Thyroglobulin during Prolonged Antarctic Residence: Effect of Thyroxine Supplement in the Polar 3,5,3′-Triiodothyronine Syndrome

Abstract: Extended Antarctic residence (AR) is associated with an increase in serum TSH, a decrease in free T(4), and an increase in T(3) production and clearance. It is not clear whether these adaptations reflect changes in clearance alone or whether intrinsic thyroidal synthetic activity also changes. Thyroglobulin (Tg) secretion is an independent marker of intrinsic thyroid activity whose kinetics are independent of those of T(3) and T(4). In this study we examined changes in Tg levels in healthy subjects before and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
1
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 21 publications
1
9
1
2
Order By: Relevance
“…*P < 0.05, Great Wall Station versus Zhongshan Station Palinkas et al 2007a;Levy et al 2013), FT4 of the Zhongshan Station crew decreased during the austral winter. Concurrently, TSH levels increased gradually until return to China, where they became statistically significant, suggesting the presence of Polar T3 Syndrome (Sawhney et al 1995;Do et al 2004). The declining levels of FT3 and FT4 prompt the hypothalamic-pituitary-thyroid (HPT) axis to produce more TSH to stimulate the increased availability of these two hormones.…”
Section: Discussionmentioning
confidence: 99%
“…*P < 0.05, Great Wall Station versus Zhongshan Station Palinkas et al 2007a;Levy et al 2013), FT4 of the Zhongshan Station crew decreased during the austral winter. Concurrently, TSH levels increased gradually until return to China, where they became statistically significant, suggesting the presence of Polar T3 Syndrome (Sawhney et al 1995;Do et al 2004). The declining levels of FT3 and FT4 prompt the hypothalamic-pituitary-thyroid (HPT) axis to produce more TSH to stimulate the increased availability of these two hormones.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, studies have shown cold-related changes in thyroid function in Antarctica, referred to as the polar triiodothyronine (T3) syndrome, characterized by an increase in serum TSH, a decrease in free T4, and an increase in T3 production and clearance. These changes have typically been associated with decreased mood and cognitive impairment ( Do et al, 2004 ; Chen et al, 2016 ). Thirdly, research across different confined and isolated contexts have suggested that psychological resilience is linked to the relative passage of time, and that a decrease tends to occur around the third quarter of the stay independent of the actual duration, as the participants realize that the mission is only half complete ( Bechtel and Berning, 1991 ).…”
Section: Introductionmentioning
confidence: 99%
“…Increases in serum TSH levels have also been observed in infants and young children during surgical hypothermia [ 15 ] . Some studies have shown prolonged arctic residence leads the increase in TSH to be associated with an increase in thyroglobulin and T3 [ 16 ] . In addition, cold exposure in animals leads to enhanced thyroid hormonal secretion, degradation, and excretion.…”
mentioning
confidence: 99%